Design with the other 90% : cities - Smith, Cynthia E.; Cooper-Hewitt Museum; United Nations (New York : Cooper-Hewitt, National Design Museum, 2011)
Through essays, interviews, and profiles of 60 examples of community-led design, this second book in an ongoing series examines the issues arising from unprecedented urban growth, primarily in the informal settlements of emerging and developing economies, as well as efforts in urban planning, sustainable design, affordable housing, entrepreneurship, nonformal education, communication, food, security, water and sanitation, and public health in these communities.
"Published on the occasion of the exhibition ... organized by Cooper-Hewitt, National Design Museum, Smithsonian Institution, and presented at the United Nations, October 15, 2011-January 9, 2012"--Colophon.
Includes bibliographical references (p. 224-225) and index.
Keywords: Industrial design -- Exhibitions -- Developing countries; Architecture